The Impact of Skipping Breakfast on the Risk of Metabolic Syndrome: A Review of the Latest Literature (Journal Nutrizione, 2025)
This review synthesizes recent evidence on the relationship between skipping breakfast and the risk of metabolic syndrome by integrating epidemiological findings, mechanistic pathways and behavioral determinants. A systematic literature review of studies published between 2014 and 2024 identified consistent associations between habitual breakfast omission and higher prevalence of central obesity, impaired glucose regulation, dyslipidemia and hypertension. Prospective cohort studies indicate that breakfast skipping and delayed first meals predict increased risk of metabolic syndrome and type 2 diabetes, even when adjusting for lifestyle confounders. Mechanistic studies highlight physiological pathways involving impaired insulin sensitivity, altered hormone secretion, circadian disruption and compensatory dietary behavior, which collectively contribute to metabolic dysregulation. However, heterogeneity across study designs, breakfast definitions and diagnostic criteria limits causal inference and underscores the need for more standardized methodologies. Public health implications include promoting regular and nutritionally balanced morning meals, addressing structural barriers to breakfast consumption and integrating meal timing into metabolic risk assessments. Future research should incorporate chronobiological measures, culturally specific analyses and objective biomarkers to clarify causal relationships more effectively. Overall, the current evidence supports the role of breakfast behavior as a meaningful factor influencing metabolic health